Disgust stimuli reduce heart rate but do not contribute to vasovagal symptoms. (June 2016) - Gilchrist, Philippe T.; Vrinceanu, Tudor; Béland, Sophie; Bacon, Simon L.; Ditto, Blaine
Abstract: Background and objectives: The vasovagal response demonstrates a unique form of stress response, common in medical settings yet provoked by a variety of blood-injury-injection stimuli. This study aimed to better understand the psychophysiological mechanisms of the vasovagal response.. Methods: 16 undergraduates with and 42 without a self-reported history of fainting watched five 3–5 min videos with different emotional content. One documentary clip (Neutral condition) described a campus environmental project while another (Blood/Injury) depicted portions of an open heart surgery. Three additional clips were also used, including Medical, Threat, and Contamination stimuli. Vasovagal symptoms and physiological variables were assessed during each video. Results: As predicted, while the disgust-related stimuli (Blood/Injury, Medical, Contamination) were associated with generally lower heart rate, the Blood/Injury video produced the highest symptoms and the only significant difference between previous fainters and non-fainters. The physiological measures also revealed that participants with a fainting history experienced higher stroke volume and lower systolic blood pressure throughout, as well as several main effects of video. Limitations: An additional decrease in systolic blood pressure and respiration produced by watching the Blood/Injury video may have been sufficient to trigger symptoms in some, though results also suggest that systemic variables do not entirely explain susceptibility to symptoms. More careful evaluation of regional blood flow may be required. Conclusions: Participants who had previously experienced strong vasovagal responses displayed what appeared to be an anticipatory response to the Blood/Injury video. Finally, disgust stimuli may reduce heart rate but do not appear to contribute to vasovagal symptoms. Graphical abstract: Highlights: We investigated the effects of emotional video stimuli on vasovagal responses. A video showing blood led to stronger symptoms than those eliciting disgust or fear. Participants with a history of fainting appear to show anticipatory responses. Results support the importance of blood stimuli in the vasovagal response.